A estratégia de comunicação organizacional, tendo como base a gestão por valores - Carvalho, Hannah de (2015)
The impact of globalization and the information age and the network society brought the social, technological and economic development by modifying the processes of communication and the strategy in organizations. In this context, companies had the need to develop new business models, as well as, with organizational communication as a strategic element, so as construction of organizational actions, as a compound of the architecture and framework for competitiveness in the business arena . The study of this application in Management by Values focused its concept directed to the person, which is based element to the first market composition and disseminator of information where the emotional and spiritual dimensions impact on your engagement profile and commitment. This dissertation analyzes the implementation of the strategy of organizational communication based on management by values, in view of the global environment, the information society and the network society